Teaching Entangled Migration Histories: The Image of Polish-Ukrainian Migrations of the 1940s in Polish History Textbooks (2000-25) - Wojtych, Tadeusz (Sensus Historiae, 2026)
Since 2022, approx. 1 million Ukrainian refugees have settled in Poland. As a result, history classrooms increasingly more often witness the encounter of different narratives on a contested past. This article is a step towards explaining how such narratives are shaped through history textbooks. I analyse how the portrayal of one element of this contested past - forced migrations of the 1940s - has been evolving in twenty-first-century Poland. I conclude that Polish textbooks pay increasingly more attention to the fate of non-Polish migrants, such as the Ukrainians resettled to Soviet Ukraine during “population exchanges” or to western Poland during Operation Vistula. At the same time, the fate of individual nations (Poles, Ukrainians etc.) takes precedence over the exploration of the parallels between the suffering of those nations. The opposite, however, can be said about supplementary teaching materials, which tend to explore stories that connect people across borders, even if these stories are contested or controversial ones.